African Solution to African Problems: AU and the Conflict Resolution in South Sudan (Politeja, 2018)
The article deals with the concept of responsibility to protect, applied on the case study of South Sudan. The introductory part of the paper discusses the concept itself, its emergence and inclusion in relevant international law documents. The second part is dedicated to the analysis of African Union’s documents which enshrine responsibility to protect concept to the organization’s politics. The third part analyses the South Sudanese civil war and is concerned with the role of African Union in the conflict resolution process in current South Sudan. Methodologically, it is an intrinsic case study and it is based on the analysis of African Union documents and relevant literature.